Transformer chaque expression en somme de nombres relatifs puis calculer

B = ( -9 ) + ( -8 ) - ( +7 ) + ( +6 ) - ( +5 ) + ( -4)
B =
B =
B =


C = ( -13 )+( -57 )- ( -24 )-( -38 )- ( -12 )+(+13)
C =
C =
C =

Bonne soiree repondez moi vite svp

2

Réponses

2013-09-30T20:33:10+02:00
B = ( -9 ) + ( -8 ) - ( +7 ) + ( +6 ) - ( +5 ) + ( -4)
B= -9 -8 -7 +6 -5 -4
B= -27

C = ( -13 )+( -57 )- ( -24 )-( -38 )- ( -12 )+(+13)
C= -13-57+24+38+12+13
C= 17
2013-09-30T20:46:08+02:00
Bonsoir

B = ( -9 ) + ( -8 ) - ( +7 ) + ( +6 ) - ( +5 ) + ( -4)
B = -9 -8 -7 +6 -5 -4
B = +6 -33
B = - 27


C = ( -13 )+( -57 )- ( -24 )-( -38 )- ( -12 )+(+13)
C = -13 -57 +24 +38 +12 +13
C = +87 - 70
C = +17